PENGARUH PENAMBAHAN N-HEKSANA PADA ADULTERASI MINYAK KELAPA SAWIT DAN MINYAK BABI TERHADAP SIFAT FISIK - Irfan Kurniawan (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2020)
Palm oil is one of the most consumed and manufactured oils in the world. This inexpensive, easy-to-produce and highly stable oil is used for a wide variety of foods, cosmetics, hygiene products, and can also be used as a source of biofuels or biodiesel. Most palm oil is manufactured in Asia, Africa and South America because oil palm trees require warm temperatures, sunlight, and high rainfall to maximize their production. Pig oil is a fat that is taken from the fatty tissue of pig animals. Pig oil can be obtained by means of extraction using the dry rendering method is a way of extracting animal oil by heating without water. This research uses the complete random draft (RAL) factorial with (2) two repeats. Factor I: Solvent concentration (K) consists of 4 levels namely: K1 = 20%, K2 = 30%, K3 = 40% and K4 = 50%. Factor II: Maceration time (W) consists of 4 levels: W1 = 06 hours, W2 = 12 hours, W3 = 18 hours and W4 = 24 hours. The observed parameters include type weights, acid numbers, iodine numbers and total microbes.